Stagnation arising through intermittent usage is associated with increased viable but non culturable Legionella and amoeba hosts in a hospital water system - Nisar, Muhammad Atif; Ros, Kirstin E.; Brown, Melissa H.; Bentham, Richard; Best, Giles; Xi, James; Hinds, Jason; Whiley, Harriet (Frontiers in Cellular and Infection Microbiology, 2023)
Hospital water systems are a significant source of Legionella, resulting in the potentially fatal Legionnaires’ disease. One of the biggest challenges for Legionella management within these systems is that under unfavorable conditions Legionella transforms itself into a viable but non culturable (VBNC) state that cannot be detected using the standard methods. This study used a novel method (flow cytometry-cell sorting and qPCR [VFC+qPCR] assay) concurrently with the standard detection methods to examine the effect of temporary water stagnation, on Legionella spp. and microbial communities present in a hospital water system. Water samples were also analyzed for amoebae using culture and Vermamoeba vermiformis and Acanthamoeba specific qPCR. The water temperature, number and duration of water flow events for the hand basins and showers sampled was measured using the Enware Smart Flow® monitoring system. qPCR analysis demonstrated that 21.8% samples were positive for Legionella spp., 21% for L. pneumophila, 40.9% for V. vermiformis and 4.2% for Acanthamoeba. All samples that were Legionella spp. positive using qPCR (22%) were also positive for VBNC Legionella spp.; however, only 2.5% of samples were positive for culturable Legionella spp. 18.1% of the samples were positive for free-living amoebae (FLA) using culture. All samples positive for Legionella spp. were also positive for FLA. Samples with a high heterotrophic plate count (HPC ≥ 5 × 103 CFU/L) were also significantly associated with high concentrations of Legionella spp. DNA, VBNC Legionella spp./L. pneumophila (p < 0.01) and V. vermiformis (p < 0.05). Temporary water stagnation arising through intermittent usage (< 2 hours of usage per month) significantly (p < 0.01) increased the amount of Legionella spp. DNA, VBNC Legionella spp./L. pneumophila, and V. vermiformis; however, it did not significantly impact the HPC load. In contrast to stagnation, no relationship was observed between the microbes and water temperature. In conclusion, Legionella spp. (DNA and VBNC) was associated with V. vermiformis, heterotrophic bacteria, and stagnation occurring through intermittent usage. This is the first study to monitor VBNC Legionella spp. within a hospital water system. The high percentage of false negative Legionella spp. results provided by the culture method supports the use of either qPCR or VFC+qPCR to monitor Legionella spp. contamination within hospital water systems.